Higher genetic diversity in recolonized areas than in refugia of Alnus glutinosa triggered by continent‐wide lineage admixture. Issue 18 (6th September 2015) - Havrdová, Alena; Douda, Jan; Krak, Karol; Vít, Petr; Hadincová, Věroslava; Zákravský, Petr; Mandák, Bohumil
Abstract Genetic admixture is supposed to be an important trigger of species expansions because it can create the potential for selection of genotypes suitable for new climatic conditions. Up until now, however, no continent‐wide population genetic study has performed a detailed reconstruction of admixture events during natural species expansions. To fill this gap, we analysed the postglacial history of Alnus glutinosa, a keystone species of European swamp habitats, across its entire distribution range using two molecular markers, cpDNA and nuclear microsatellites. CpDNA revealed multiple southern refugia located in the Iberian, Apennine, Balkan and Anatolian Peninsulas, Corsica and North Africa. Analysis of microsatellites variation revealed three main directions of postglacial expansion: (i) from the northern part of the Iberian Peninsula to Western and Central Europe and subsequently to the British Isles, (ii) from the Apennine Peninsula to the Alps and (iii) from the eastern part of the Balkan Peninsula to the Carpathians followed by expansion towards the Northern European plains. This challenges the classical paradigm that most European populations originated from refugial areas in the Carpathians. It has been shown that colonizing lineages have met several times and formed secondary contact zones with unexpectedly high population genetic diversity in Central Europe and Scandinavia. On the contrary, limited genetic admixture in southern refugial areas of A. glutinosa renders rear‐edge populations in the Mediterranean region more vulnerable to extinction due to climate change.